Ungrounded empires : the cultural politics of modern Chinese transnationalism - Ong, Aihwa; Nonini, Donald Macon (Routledge, 1997)
This book examines Chinese transnationalism as a distinctive domain within the new 'flexible' capitalism emerging in the Asia-Pacific region. It is based on new ethnographic research and interweaves anthropology, culture and politics.